Experimental Study on Adsorption Pore Structure and Gas Migration of Coal Reservoir Using Low-Field Nuclear Magnetic Resonance - Jiazhuo Li; Penghui Guo; Wenhao Xie; Jiaqi Chu; Zhiqiang Yin; Anying Yuan; Ming Zhang; Zhenhua Jiao (Advances in Civil Engineering)
For the quantitative recognition and characterization of the flow characteristics of polymorphism coalbed gas in tectonic coal, experiments on pore morphology, pore diameter distribution, and methane adsorption law in outburst tectonic coal were carried out by field emission scanning electron microscopy and low-field nuclear magnetic resonance. The results revealed abundant round and dense “pyrolysis pores” in outburst tectonic coals, most of which were adsorption and seepage pores, with micropores accounting for 78.2%. Most pores were independent and formed the network pore space for gas enrichment and migration in outburst tectonic coal. The transverse relaxation time (T2) of methane adsorption in tectonic coal and crushed outburst tectonic coals presented three peaks, namely, adsorption, drifting, and free peaks. The isolation of nanopores and micropores revealed lower adsorption capacity of outburst tectonic coal than that of crushed outburst tectonic coal. The gas staged adsorption of raw coal with outburst tectonic low-permeability was observed. Under low gas pressure, the T2 spectral peak area of methane adsorption increased remarkably, whereas that of desorbed methane increased slightly. As gas pressure was increased to a certain numerical value, the increment of methane adsorption decreased and tended to reach equilibrium. This finding reflected that methane adsorption tended to be saturated after gas pressure reached a certain value, but desorbed methane in isolated micropores increased quickly. The quantitative recognition and characterization of pore structure and gas adsorption in tectonic low-permeability outburst coal seams based on low-field magnetic resonance imaging provide an experimental method for gas exploitation in coal seams and the study and control of coal and gas outburst mechanism.